Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jhbp.815
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of 5‐year recurrence‐free survival after surgery in pancreatic ductal adenocarcinoma

Abstract: Background/Purpose Pancreatic ductal adenocarcinoma (PDAC) is regarded as incurable, with a limited survival rate after curative resection. The aim of this study was to explore long‐term survival and late recurrence of PDAC after surgery. Methods Medical data of 859 patients who underwent resection between 1995 and 2014 were retrospectively examined. The clinicopathological features of the 5‐year recurrence‐free survivors and the patients with recurrent disease after 5 years were investigated separately. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…Elevated NLR was shown to predict a poor prognosis in some studies [ 6 ]; however, only PLR was a significant risk factor in other studies [ 7 ]. In our previous single institutional study, both NLR and PLR were associated with the OS of patients with resected PDAC [ 2 ]. In the present study based on multi-center data, only PLR was significantly associated with RFS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated NLR was shown to predict a poor prognosis in some studies [ 6 ]; however, only PLR was a significant risk factor in other studies [ 7 ]. In our previous single institutional study, both NLR and PLR were associated with the OS of patients with resected PDAC [ 2 ]. In the present study based on multi-center data, only PLR was significantly associated with RFS.…”
Section: Discussionmentioning
confidence: 99%
“…The only curative treatment is surgical resection. As reported in recent studies, five-year survival for patients with resected PDAC has increased up to 17% [ 2 ]. The most widely accepted method for predicting survival outcomes after surgery is the American Joint Committee on Cancer (AJCC) system, consisting of tumor extent (T stage), lymph node status (N stage), and distant metastasis (M stage) (TNM staging) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if R0 resection is achieved, more than half of patients subsequently experience local recurrence or distant metastases within 2 years of surgery ( Kim et al, 2017 ; Strobel et al, 2017 ; Ghaneh et al, 2019 ; Tummers et al, 2019 ). Clinical features including but not limited to tumor size and tumor grade have been associated with tumor recurrence ( Abe et al, 2020 ; Kim et al, 2020 ; Yoon et al, 2020 ); nevertheless, their predictive ability was not always satisfactory in R0-treated patients. Effective prediction of recurrence may help to tailor adjuvant chemotherapy and postoperative surveillance in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In this context, prognostic analyses in patients with pancreatic cancer (PC) who received various treatments, including pancreatectomy, have been conducted. [3][4][5][6] However, significant limitations have been noted in the conventional prognostic evaluation: a high frequency of poor prognostic factors was observed even in the subgroup of longterm survivors. 3,4,7,8 Indeed, Strobel et al reported that 63% of 5-year survivors were positive for nodal status, which is a wellknown poor prognostic variable in PC.…”
mentioning
confidence: 99%